Peningkatan Keterampilan Pemahaman Calistung Pada Anak Rumah Literasi Ranggi - Jauzarafa, Felisa; Suriadi, Agus; Utama Ritonga, Fajar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Calistung (reading, writing, arithmetic) is a fundamental skill set crucial for elementary school children as it forms the primary foundation of education. Mastering calistung aids in developing cognitive abilities, communication skills, and self-directed learning. Additionally, calistung enhances self-confidence, prepares children for daily life, and their professional future. Calistung education also plays a role in reducing educational inequality. Therefore, special attention from educators and parents in teaching calistung from an early age is essential to support both academic and personal development. During the Field Work Practice conducted at Rumah Literasi Ranggi, the author encountered several cases of children experiencing delays in calistung. As a result, the author assisted and facilitated these children in learning calistung during the internship period. With the goal of improving basic skills, strengthening self-confidence, developing cognitive skills, facilitating adaptation to formal education, enhancing social and emotional skills, supporting fine motor development, and adjusting learning approaches. By achieving these objectives, these children will be better prepared for further education and function more effectively in daily life.